Phenology, growing degree-days and phasic development model of wheat (Triticum aestivum) under rice (Oryza sativa )-wheat cropping system - SINGH, A K; TRIPATHI, PADMAKAR; MISHRA, S R (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during the winter season of 1997-98 and 1998-99 at Faizabad, to study the phenology, growing degree-days (GDD) and phasic development model of wheat (Triticum aeslivum L. emend. Fiori & Paol.) in rice (Oryza sativa L.) - wheat cropping system. The crop sown on 25 November took more number of days from sowing to maturity than later sowings and the duration consistently reduced with subsequent delay in sowing. Late sowing reduced the duration of vegetative and reproductive growth by 17 days. Different genotypes did not differ markedly with respect to duration during vegetati ve and reproductive phases of wheat. The thermal units accumulated to reach the physiological maturity from sowing ranged from 1 542.9 to 1 610.3 degree celcius day, with its maximum value recorded in carlier sowing (25 November) and from 1 539.9 to 1 620.4 degree celcius day in different genotypes averaged over dates of sowing. A decreasing trend in accumulated growing degree-days with delay in sowing was notked. Based on the phenophase data of 2 years for 3 sowing dates and 3 genotypes, a regression model could be develped to predict the onset of any particular phenophase in the crop period.